A Juxtapose of Symmetric Block Cipher Algorithms to Control, Analyse and Augment Efficiency of IoT Enabled Devices - K. Savima (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The neoteric times have contrived the utilization of automated functionalities and Internet of Things (IoT) enabled devices for quotidian working. With the increase in engaging physical entities with the virtual technologies, and the collaborative conjunction that has augmented the quality of life, it is quite natural for individuals to implement a paradigm shift in terms of upgrading to IoT enabled entities. Nonetheless, while it creates facile resolutions, the security of devices and data are under enormous risk. Hacking and data pilferage are most often evinced due to the incapability of IoT devices to sufficiently manage storage, integration, communication and the computational complexity that persists between the devices. Block cipher cryptography is a swift-developing domain that enhances the integrity of resources and mitigates intricacy in integrating the diverse operations, along with enhancing the security of functions that is usually carelessly neglected by the conventional processing devices. The previous studies relevant to this field of interest have incorporated the use of hardware services and the functionality of block ciphers to analyse their compatibility with IoT devices. However, this paper focuses to elaborate on a comparative algorithmic implementation of block ciphers to render a scrutinization from three algorithmic processes that dissect the efficiency of security. Rivest-Shamir-Adleman (RSA) algorithm with asymmetric cryptography, and an enhanced key generation of multiples of 256 is incorporated with base 64 encryption and decryption. The processing time in relevance to the encryption methods, and the effective utilization of Pseudorandom Permutational (PRP) technique that further complements the resilience of IoT devices is meticulously employed in this study. The cryptanalysis performed with Reverse, Caesar cipher and columnar- transpositional encoding mechanisms aid to analyse the efficacy of encryption and decryption to supplement competent protection of IoT devices. The simulations for the proposed study is implemented in Python, and the results are successfully procured.